Advanced Concepts in Endocarditis 2021 - Firstenberg, Michael S.; Lakshmanadoss, Umashankar (IntechOpen, 2021)
The concept of endocarditis has evolved significantly over the years. While initially associated with patients with advanced co-morbidities, such as renal failure and chronic immunosuppression, endocarditis now spans many diverse disciplines. As such, the importance of advanced diagnostic imagining tools, a better understanding of the pathophysiology of not only the infectious (and non-infectious) disease process but also of cardiac structural abnormalities, and the growing literature on management cannot be underemphasized. This book broadens our collective understanding of the spectrum of diagnostic and therapeutic challenges that all areas of medicine must appreciate when faced with the challenging clinical problem of endocarditis.